Structural Model of Maternal Behavior in Community Setting to Prevent Low Birth Weight in East Nusa Tenggara, Indonesia - Anggrahini, Simplicia Maria; Notobroto, Hari Basuki; Irwanto, Irwanto; Suryawan, Ahmad (Folia Medica Indonesiana, 2020)
Low birth weight (LBW) is still a magnitude problem in Indonesia with a multifactorial causes. Studies revealed that one of cause of LBW-infants birth is mother's behavior in treating her pregnancy, including traditional pregnancy care practices. The purpose was to develop the structural model on community setting that might describe the LBW infants-birth. A case-control study on 50 post-partum mothers with LBW and 50 with normal birthweight infants was held in Kupang, East Nusa Tenggara, Indonesia, November 2016 - May 2017. Mother who have spontaneous birth, singleton, and received integrated ANC were inlcuded. Several data such as maternal characteristics, pregnancy knowledge, perceived behavioral control (PBC), maternal health status, obedience to traditional pregnancy care, were collected using questionnaire and medical records tracing. Statistical analysis was performed using path analysis from SmartPLS 3.2.7 and considered significant path when the coefficients were not zero with P value <0.05. Outer and inner model analysis showed two significant paths, both are come from maternal characteristic that influence the LBW infants-birth through pregnancy knowledge (0.489, P=0.000) and PBC (0,425, P=0,000). In the first path, PBC affect maternal health status (0.217, P=0.021) which in turn will cause LBW (0.201, P=0.001). The second path, PBC affect the obedience to traditional pregnancy care (0.474, P=0.000) and then influence to LBW (0.316, P=0.000). As conclusion, maternal characteristics, pregnancy knowledge, PBC, maternal health status, and obedience to traditional pregnancy care are key points that might be used as a significant variables in preventing LBW-infants birth.